The cephalopod prey of the Weddell seal, Leptonychotes weddellii, a biological sampler of the Antarctic marine ecosystem - Negri, Agustina; Daneri, Gustavo Adolfo; Ceia, F.; Vieira, R.; Cherel, Y.; Coria, N. R.; Corbalán, A.; Xavier, J. C. (Polar Biology)
Weddell seals, Leptonychotes weddellii, are important apex predators in the food web of the Antarctic marine ecosystem. However, detailed information on their trophic relationships with cephalopods is scarce. Moreover, cephalopods play a key role in the marine environment, but knowledge of their feeding habits is limited by lack of data. Here, we have combined the use of this seal as a biological sampler together with measurements of the stable isotopic signature of the beaks of their cephalopod prey. Thus, the aims of the present study were: (1) to examine in detail the cephalopod portion of the diet of Weddell seals by means of scat analysis and (2) to assess the habitat use and trophic level of the different cephalopod prey taxa identified. From January to February 2009, a total of 48 faecal droppings were collected at Hope Bay, Antarctic Peninsula. Cephalopods were mainly represented by beaks (n = 83) which were identified to the lowest possible taxonomic level. Furthermore, subsamples of beaks were separated for further isotopic analysis. Relative abundance of stable isotopes of carbon (δ13C) and nitrogen (δ15N) was determined by continuous-flow isotope-ratio mass spectrometry. Cephalopods were represented uniquely by octopods of the subfamily Eledoninae. Pareledone turqueti was the dominant prey species followed by the papillated Pareledone species group and Adelieledone polymorpha. We conclude that Weddell seals preyed primarily on benthic prey resources. Furthermore, the relatively similar δ13C and δ15N values in beaks of the three octopod prey taxa suggest that these share the same type of habitat and occupy similar trophic level positions. Fil: Negri, Agustina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Daneri, ...